The Fluctuation Niche in Plants. (9th August 2009) - Terradas, Jaume; Peñuelas, Josep; Lloret, Francisco
Abstract : Classical approaches to niche in coexisting plants have undervalued temporal fluctuations. We propose that fluctuation niche is an important dimension of the total niche and interacts with habitat and life-history niches to provide a better understanding of the multidimensional niche space where ecological interactions occur. To scale a fluctuation niche, it is necessary to relate environmental constrictions or species performance not only to the absolute values of the usual environmental and ecophysiological variables but also to their variances or other measures of variability. We use Mediterranean plant communities as examples, because they present characteristic large seasonal and interannual fluctuations in water and nutrient availabilities, along an episodic-constant gradient, and because the plant responses include a number of syndromes coupled to this gradient.